Long-term outcomes of untreated buccal gingival recessions: a systematic review and meta-analysis (2016)
Background: This review aims to: 1) assess the long‐term outcomes of untreated buccal gingival recession (GR) defects and the associated reported esthetic and functional alterations; and 2) evaluate which factors influence the progression/worsening of dental and periodontal tissue conditions of untreated GR defects. Methods: Interventional and observational studies with duration of ≥24 months reporting outcomes from adult patients with localized or multiple GR defects not treated by root coverage or gingival augmentation procedures were considered eligible for inclusion. MEDLINE and EMBASE databases were searched for articles published through July 2015. Random‐effects meta‐analyses were performed comparing baseline versus most recent follow‐up outcomes (i.e., number of patients with ≥1 GR and number of sites with GR). Results: Of 378 potentially eligible articles, eight (reporting six studies) met inclusion criteria. Of 1,647 GR defects with baseline and follow‐up information, 78.1% experienced GR depth increase during the follow‐up period, whereas the remaining experienced decrease or no change. Moreover, there was a 79.3% increase in the number of GR defects among the patients followed (i.e., new GR defects). Pooled estimates (data from four studies) showed significantly increased odds of recession development long term, regarding either number of patients (odds ratio 2.43; P = 0.03) or number of sites with GR (odds ratio 2.16; P = 0.0005). Conclusion: Untreated recession defects in individuals with good oral hygiene have a high probability of progressing during long‐term follow‐up.